Implikasi Vacum Of Norm Nafkah Lampau Anak Di Indonesia - Azmi, Miftahudin; Habibah, Idha Nur; Syafiuddin, M. Nur; ’El-Syafi, Lucky Eka Khalis Aulia (Judex Laguens, 2023)
There is no legal arrangement regarding the fulfillment of the child's right to a living which his biological father neglects to lead to the pattern of child protection in Indonesia. This paper aims to describe and analyze the sociological implications of the absence of regulation of the fulfillment of the last living right to the pattern of child protection in Indonesia. This research includes normative juridical research with a philosophical approach and legislation and analysis with analytical prescriptive methods, hermenautics (interpretation) of law and ijtihadi. The results of the study show that there are two implications of no legal regulation of the fulfillment of children's rights to the last living on the pattern of child protection in Indonesia, namely: the occurrence of disharmony in the relationship between children and their biological fathers and the degradation of the fulfillment of children's rights from their biological fathers.